Time Effect of Chloride Erosion on Physical and Mechanical Properties of High-Water-Content Materials - Hai-kuan Wu; Chang-wu Liu; Zhao Zhang; Yi-chen Miao (Advances in Materials Science and Engineering)
In order to study the characteristics of high water-content materials (HWC) undergoing chloride erosion, we analyzed and summarized changes in strength, elastic modulus, and mass of HWC materials during chloride erosion using specific experimental research, and we also described the compression failure morphologies of HWC materials after erosion. The cuboid specimens developed a horizontal crack between the top and bottom, and the cylindrical specimens developed irregular encryption cracks at the top during increasing pressure. The erosion of HWC materials exposed to calcium chloride (CaCl2) solutions was relatively serious, and the erosion of the cuboid specimens was lower than that of the cylindrical specimens. The strength of HWC materials increased during prolonged erosion, and the strength of the cylindrical specimens in water was the highest, followed by the CaCl2 and sodium chloride (NaCl) solutions. However, the strength change of the cuboid specimens after 28 d was contrary to the above order. In late erosion stages, the HWC materials had better compactness and experienced smaller compressive deformation in water than the other two solutions. In the NaCl solution, the high-water filling material had more pores and a larger deformation than the other solutions.